BLUEPRINT FOR RECORDING DATA ON RED ONION FARMING ACTIVITIES USING THE BPR METHOD - Muhammad Riza Noor Saputra; Farrikh Alzami; Kukuh Biyantama; Muhammad Ridho Abdillah; Alvin Steven; Chaerul Umam; Aris Nurhindarto; Firman Wahyudi (Informatika, Universitas Jenderal Soedirman, 2023)
To advance agriculture in Indonesia, farmers must be able to calculate the need for fertilizer, optimal use of pesticides, the amount of irrigation water required, the type of seed and the suitable land area in order to get maximum and sustainable agricultural yields. Besides that, farmers must also know the efforts in preventing and handling diseases. Therefore, researchers developed a prototype for recording data on agricultural activities both carried out by farmers and recording the condition of agricultural land by IOT. The Business Process Reengineering method is used to obtain an AS-IS system analysis so that a blueprint model is obtained that is suitable for recording agricultural activities. So that red onion farmers can manage customer relationships while performing their agricultural activities using this web-based information system application prototype. The results of the recording carried out by farmers and IOT using the Laravel web-based application development and using PostgreSQL version 14 can be used to provide input and notifications to farmers regarding actions that need to be taken.